Bundled software development for concurrent cardiac performance modeling - Еремеев, Богдан Николаевич (Eastern-European Journal of Enterprise Technologies, 2014)
Tasks of timely identification and correction of cardiac disturbances are associated with searching for quantitative laws of changing hemodynamic and electrical parameters, as well as with the analysis of asynchronous concurrent processes and their interaction. To solve this problem, it was proposed to use specialized modeling complex with a combined model of the heart, which is a graphical-analytical model of the heart, where certain graphical elements are described by local empirical models. In this case, the built-in mobile solutions, based on Android operating system were proposed to useas a platform for the software implementation, which provided easy integration into existing or newly developed diagnostic systems.To simplify the process of construction and interpretation of the parameters of the studied object, it was proposed to use hierarchical approach, using the opportunity to accommodate submodels in peaks of macro-transitions. Herewith, activation of such a transition is characterized by performing a session of submodel, accommodated in it. This approach has allowed to form a layered structure with indicating inter-level relations, having ensured the adaptation of the model to changes in the level of detail. A study design that displays the processing and interaction of the input signal with graphical-analytical level of the cardiac performance model with further output of the results was presented in the paper. Development of the «Heart Expert» modeling complex will enable the construction, operation and testing of the created models. Thus, we have got an opportunity to distribute the computational and functional parts of the model, with individual adjustment of their parameters and implementation. This simplifies the process of constructing and analyzing the models of complex physiological systems of the body, thus providing a unification ofthe model creation at all its levels.